2015
DOI: 10.1007/s00253-015-6873-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of hydrolases from hydrothermal vent sediments of the Levante Bay, Vulcano Island (Aeolian archipelago) identified by activity-based metagenomics and biochemical characterization of new esterases and an arabinopyranosidase

Abstract: A metagenomic fosmid expression library established from environmental DNA (eDNA) from the shallow hot vent sediment sample collected from the Levante Bay, Vulcano Island (Aeolian archipelago) was established in Escherichia coli. Using activity-based screening assays, we have assessed 9600 fosmid clones corresponding to approximately 350 Mbp of the cloned eDNA, for the lipases/esterases/lactamases, haloalkane and haloacid dehalogenases, and glycoside hydrolases. Thirty-four positive fosmid clones were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 53 publications
0
33
1
Order By: Relevance
“…The use of metagenomics, the study of whole communities’ genomes, has proven to be a useful tool for the discovery of novel cellulases, both in the functional and the sequence-based approaches [ 10 , 11 ]. Several studies had found cellulases in a wide variety of natural thermophilic environments, such as hydrothermal vents [ 56 , 57 ], continental geothermal pools and hotsprings [ 58 , 59 ], and man-made environments like vermicompost [ 60 ], compost [ 37 , 61 , 62 ], and biogas digesters [ 63 ]. Nevertheless, high-temperature acting enzymes have also been found by metagenomics on moderate-temperature samples like soils [ 40 , 64 , 65 ] and aquatic environments [ 66 ], and in microorganisms associated with animals like microbial communities in rabbit cecum [ 67 ], ruminants rumen [ 36 , 68 , 69 ], earthworm casts [ 70 ], and thermite guts [ 71 , 72 ].…”
Section: Metagenomics For the Search Of Novel Cellulasesmentioning
confidence: 99%
“…The use of metagenomics, the study of whole communities’ genomes, has proven to be a useful tool for the discovery of novel cellulases, both in the functional and the sequence-based approaches [ 10 , 11 ]. Several studies had found cellulases in a wide variety of natural thermophilic environments, such as hydrothermal vents [ 56 , 57 ], continental geothermal pools and hotsprings [ 58 , 59 ], and man-made environments like vermicompost [ 60 ], compost [ 37 , 61 , 62 ], and biogas digesters [ 63 ]. Nevertheless, high-temperature acting enzymes have also been found by metagenomics on moderate-temperature samples like soils [ 40 , 64 , 65 ] and aquatic environments [ 66 ], and in microorganisms associated with animals like microbial communities in rabbit cecum [ 67 ], ruminants rumen [ 36 , 68 , 69 ], earthworm casts [ 70 ], and thermite guts [ 71 , 72 ].…”
Section: Metagenomics For the Search Of Novel Cellulasesmentioning
confidence: 99%
“…Using (R,S)-1-phenylethyl acetate, Im-LipG9 (KM023399) showed excellent enantio-selectivity for the R-isomer (E > 200), giving an ee of higher than 95% for the products at 49% conversion. Using a racemic mixture, the capacity to hydrolyze preferentially (S)-racemic ofloxacin butyl ester with an ee of 70.3% was found using an esterase ( (KP861227), LIPESV12_26 (KP861228) from hydrothermal vent sediments of the Levante Bay (Placido et al 2015) were also found to be enantio-selective, to different degrees and preferences, for at least eight chiral esters, including methyl-(±)-mandelate, methyl-(±)-lactate, (±)-menthylacetate, (±)-neomenthyl acetate, (±)-glycidyl 4-nitrobenzoate, (±)-pantolactone, and (±)-methyl -3-hydroxybutyrate.…”
Section: Hydrolytic Activitiesmentioning
confidence: 99%
“…Hydrolysis of aryl esters such as methyl phenyl-acetate and phenyl acetate have also been from hydrothermal vent sediments (Placido et al 2015), and 5 cold-active and salt-resistant esterases (JX133669, JX133670, JX133672-JX133675) from marine metagenomes (Tchigvintsev et al 2015). These studies demonstrated that esterases/lipases discovered in metagenomes show reactivity and promiscuity levels that are superior to those of the homologous hydrolases reported to date.…”
Section: Hydrolytic Activitiesmentioning
confidence: 99%
“…Coverage depth is typically high and levels of sequence redundancy within relatively short (typically <45kbp) inserts are expected, in general, to be low. Indeed, costs associated with sequencing can be further reduced by sequencing libraries of pooled inserts [ 15 17 ]. Lam et al used pooled and individually sequenced inserts to provide a detailed evaluation of this approach [ 16 ], demonstrating that many inserts could be completely or almost completely assembled in one or two fragments and assigned to their clones of origin through Sanger sequencing of the original insert ends (end-tag sequencing).…”
Section: Introductionmentioning
confidence: 99%